Assessment of the potential utility of different regions of Streptococcus uberis adhesion molecule (SUAM) for mastitis subunit vaccine development. (April 2017) - Perrig, Melina Soledad; Veaute, Carolina; Renna, María Sol; Pujato, Nazarena; Calvinho, Luis; Marcipar, Iván; Barbagelata, María Sol
Abstract: Streptococcus uberis is one of the most prevalent pathogens causing clinical and subclinical mastitis worldwide. Among bacterial factors involved in intramammary infections caused by this organism, S. uberis adhesion molecule (SUAM) is one of the main virulence factors identified. This molecule is involved in S. uberis internalization to mammary epithelial cells through lactoferrin (Lf) binding. The objective of this study was to evaluate SUAM properties as a potential subunit vaccine component for prevention of S. uberis mastitis. B epitope prediction analysis of SUAM sequence was used to identify potentially immunogenic regions. Since these regions were detected all along the gene, this criterion did not allow selecting a specific region as a potential immunogen. Hence, four fractions of SUAM (-1fr, 2fr, 3fr and 4fr), comprising most of the protein, were cloned and expressed. Every fraction elicited a humoral immune response in mice as predicted by bioinformatics analysis. SUAM-1fr generated antibodies with the highest recognition ability towards SUAM native protein. Moreover, antibodies against SUAM-1fr produced the highest proportion of internalization inhibition of S. uberis to mammary epithelial cells. In conclusion, SUAM immunogenic and functionally relevant regions were identified and allowed to propose SUAM-1fr as a potential candidate for a subunit vaccine for S. uberis mastitis prevention. Highlights: SUAM possess potentially immunogenic regions all along the gene. SUAM44-282 generated antibodies with the highest recognition ability towards SUAM wt . Antibodies against SUAM44-282 reduced a 81% the adhesion-internalization of bacteria to MAC-T cells.